Uji Identifikasi Farmakognostik Tumbuhan Kemiri Sunan (Aleurites trisperma) di Kebun Percobaan Universitas Muhammadiyah Palangkaraya - Rabiatul Adawiyah (Anterior Jurnal, 2017)
Natural ingredients have been known and used all over the world for thousands of years ago. In Indonesia, the natural ingredients, better known as herbal or traditional medicine, has been widespread since the time of the ancestors until now and continues to be preserved as a cultural heritage. The wealth of natural resources that we have is an asset of future development, the problem is how we can exploit that potential wisely and wisely. Siri herbs (Aleurites trisperma) is one of the plants in Indonesia. Pecan sunan (Aleurites trisperma) is the name of the plant given to the plant species of pecan poison. In middle Kalimantan this plant has started cultivated in the field of agriculture as bioindustry and pesticide, there has been no research of the plant is used as a treatment. This study aims to obtain scientific data about the pharmacognostic picture of the hazelnut plants and to enrich the inventory of Indonesian medicinal plants, knowing the simplicia chemicals group of candlenut crops. The method used is experimental research with laboratory approach. The research was conducted with several stages of macroscopic, microscopic and leafy leaves extract obtained by maceration method and fatty test using soxhletation using 96% ethanol solvent. The results of the study on green leaf organoleptic, soft odor (no sting), tasting (preliminary), preliminary test of water content 13.09%, ash 0.9%, fat content 7.46%, crude fiber content 32.82% and phytochemical screening results showed the chemical content of positive sugars leaves contains tannins, alkaloids, saponins, steroids, and terpenoids.